Effect of ageing and RAP content on the induction healing properties of asphalt mixtures. (10th August 2018) - Gómez-Meijide, Breixo; Ajam, Harith; Lastra-González, Pedro; Garcia, Alvaro
Highlights: Effect of ageing and RAP content in the healing capacity of asphalt mix was assessed. Both factors reduce effectiveness and energy efficiency of induction healing. Both factors reduce density and increase the air voids content in compacted mixes. Healing of mixes with high compaction level is worse. Correlations between ageing days and RAP content were found. Abstract: Over the service life of asphalt roads, different factors produce, in the bitumen, a hardening process known as "ageing". Also, the addition of recycled, aged material (i.e. RAP) to new mixes modifies the viscosity of the mix. The present research studies how these two actions affect the capacity for healing, by electromagnetic induction, of asphalt mixes. Mixes subjected to different ageing processes or containing different amounts of RAP were tested. Results show that both ageing, and RAP content contribute to increasing binder stiffness and air voids content in the mix. Therefore, the healing process becomes less effective and energy efficient.